(untitled) (Revista Venezolana de Salud Pública, 2018)
Health conceived as a complex phenomenon constitutes a circuit where the effects retroact on the causes and the health disease process as a product, reproduces its causes in a reiterative way so its approach should not be made from a simplified but multidimensional and interdisciplinary logic. In the same way, the paradigm of complexity proposes to articulate the interdependencies of disciplinary or specialized knowledge, and conceives an organization or systemic complexity between the whole and the parts, which allows it to be capable of self-echo-reproduction and regeneration when relating to others. with its environment or environment. Under this approach, public health becomes a crucible where many disciplines can converge to understand and address the problems that affect the well-being of the population from that complex view of their environment that includes the physical, psychological, anthroposocial, spiritual, cultural and the politically and ideologically constructed